Gastronomic Tourism for Sustainable Growth in Jambi - Lubis, Tona Aurora; Nizori, Addion; Firmansyah, Firmansyah; Dewi , Erwita; Ningsih, Maryati (Transpublika Publisher, 2024)
This study investigates the interplay among gastronomic tourism development, business governance, and business performance in Jambi Province, focusing on leveraging Malay cultural identity to enhance the regional gastronomy sector. Employing a quantitative methodology with Partial Least Squares Structural Equation Modeling (PLS-SEM), data from 150 local gastronomy business respondents were analyzed. The findings reveal that gastronomic tourism development significantly improves business governance and performance. However, a complex negative relationship exists between rigid governance practices and business performance, indicating the need for flexible frameworks that accommodate the operational realities of small and medium-sized enterprises (SMEs). Gastronomic tourism fosters transparency, accountability, and stakeholder collaboration, driven by innovations and the preservation of Malay culinary heritage. This study highlights gastronomy as a vital cultural and economic asset, offering a model that integrates cultural preservation with governance improvements to achieve sustainable outcomes. Positioning Jambi Province as a leading gastronomic destination can catalyze economic growth and resilience. Recommendations include fostering adaptive governance models for SMEs and strengthening partnerships among policymakers, local communities, and businesses to harness the region’s full gastronomic potential. These findings provide practical insights for enhancing competitiveness and sustainability in Indonesia’s gastronomic tourism sector.